English Pre-service Teachers’ Perception of Anxiety in Peer Teaching: A Case Study at Universitas Kristen Indonesia - Maulimora, Veronica Novembrin (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2019)
Anxieties that are experienced by the teachers are also undergone by the pre-service teachers. The pre-service teachers feel anxious when they teach students or their peers in a real classroom. This study aimed at investigating English pre-service teachers’ perceptions of anxiety in peer teaching. To achieve the objective, a questionnaire and open-ended questions were administered to gauge the perceptions of 44 pre-service teachers of the English Education Department, Faculty of Education and Teacher Training, Universitas Kristen Indonesia. Findings revealed that the majority of the preservice English teachers felt anxious about their first peer teaching practice. It was shown that pre-service teachers were unconfident; worried about their English language skills, teaching skills, evaluation skills, and classroom management; and were not sure of the preparations they had made. The top factor causing their anxiety was their classroom management skills. This means that they put the greatest concern on the way they would manage the class. Nevertheless, by knowing the causes of the anxiety, they got the opportunities to reduce it in the next teaching.